2016
DOI: 10.1093/eurpub/ckw193
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the quality of life of chronic dialysis patients

Abstract: Patients on dialysis have moderate-to-low AI. AI is an independent predictor positively correlated with QoL in all domains except for social relationships. The social and psychological support for dialyzed patient might improve their HRQoL and illness acceptance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 5 publications
2
31
0
1
Order By: Relevance
“…It might be that frailty was the most significant limitation in taking up physical activity, and therefore it weakened the effect of adequate coping. However, this observation should be treated cautiously, since several authors observed that acceptance of the disease and treatment methods is necessary for patients to continue with therapy and comply with the doctor’s recommendations [71,72,73]. Other authors point out that disease acceptance is an independent factor positively correlated with quality of life (QoL) [74,75].…”
Section: Discussionmentioning
confidence: 99%
“…It might be that frailty was the most significant limitation in taking up physical activity, and therefore it weakened the effect of adequate coping. However, this observation should be treated cautiously, since several authors observed that acceptance of the disease and treatment methods is necessary for patients to continue with therapy and comply with the doctor’s recommendations [71,72,73]. Other authors point out that disease acceptance is an independent factor positively correlated with quality of life (QoL) [74,75].…”
Section: Discussionmentioning
confidence: 99%
“…Another reason may be the degree of illness acceptance. Jankowska-Polanska et al [19] proposed the concept of illness acceptance: the higher the degree of illness acceptance, the greater the QOL. Although their study mainly focused on HD patients, we can further infer that patients with high degrees of illness acceptance will actively seek quality medical care and cooperate with medical instructions or health education.…”
Section: Socioeconomicmentioning
confidence: 99%
“…19 The QoL of patients should be a focus during HD treatment and assisting patients in accepting their illness is proposed as a way to achieve this goal. 21 Few studies have highlighted the importance of the role of patients' acceptance of their illness as a factor in their QoL, 22 depression and anxiety, 10 or physical and mental health-related QoL in HD patients. 21 Studies have agreed that acceptance is responsible for lower anxiety and depression as well as a better QoL.…”
Section: Introductionmentioning
confidence: 99%